TRANSFORMASI STRATEGI KOMUNIKASI KORPORASI DI ERA INDUSTRI 4.0 PADA PT. KOMPAS GRAMEDIA: KAJIAN SYSTEMATIC LITERATURE REVIEW - Olvi Vania; Qonitha Risky (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
The Industrial Era 4.0 has driven major changes in the way corporations implement their communication strategies. Digital technology, social media, and big data have disrupted conventional communication approaches. This study uses a Systematic Literature Review (SLR) approach to examine the transformation of corporate communication strategies that are relevant in the context of PT. Kompas Gramedia. The aim is to identify trends, challenges, and opportunities in corporate communication in the digital era, and how PT. Kompas Gramedia as a leading media and publishing company in Indonesia responds to these dynamics. This study uses scientific articles and trusted sources published between 2013 and 2023. Researchers found related articles using Publish or Perish and the help of other applications such as Mendeley and Microsoft Excel which were then filtered into 35 selected articles for descriptive analysis. The results of the study show that corporate communication transformation includes the integration of digital technology, value-based storytelling strategies, and adaptation to social media platforms and data analytics.